Pediatric emergency department visits for pedestrian injuries in relation to the enactment of Complete Streets policy - Wells, Jordee M.; Yi, Honggang; Yang, Jingzhen; Mooney, Stephen J.; Quistberg, Alex; Leonard, Julie C. (Frontiers in Public Health, 2023)
Introduction. This study aims to evaluate the rate of pediatric Emergency Department (ED) visits for pedestrian injuries in relation to the enactment of Complete Streets policy. Methods. National Complete Streets policies were codified by county and associated with each hospital's catchment area and date of enactment. Pedestrian injury-related ED visits were identified across 40 children's hospitals within the Pediatric Health Information System (PHIS) from 2004-2014. We calculated the proportion of the PHIS hospitals' catchment areas covered by any county policy. We used a generalized linear modeling to assess the impact of the proportion of the policy coverage on the rate of pedestrian injury-related ED visits. Results. The proportion of the population covered by Complete Streets policies increased by 23.9% and pedestrian injury rates at PHIS hospitals decreased by 29.8% during the study period. After controlling for year, pediatric ED visits for pedestrian injuries did not change with increases in the PHIS catchment population with enacted Complete Streets policies. Conclusions. After accounting for time trends, Complete Streets policy enactment was not related to observed changes in ED visits for pedestrian injuries at PHIS hospitals.